Spiraea cantoniensis Reeve's Spiraea, Bridal-Wreath - Edward Gilman (EDIS)
This document provides a comprehensive overview of Spiraea cantoniensis, commonly known as Reeve’s Spiraea or Bridal-Wreath. It details the plant’s characteristics, including its fine-textured, small leaves and dense clusters of pure white flowers that bloom in spring. The document discusses the plant’s growth habits, preferred growing conditions, and potential uses in landscaping, such as mass plantings, specimen plants, and hedges. Additionally, it addresses the plant’s moderate drought tolerance, soil preferences, and minimal pest issues, making it a versatile and attractive option for various garden settings. Original publication date October 1999.